Electrowetting display with low driving voltage and preparation method thereof

Through the design of the multi -layer dielectric hydrophobic layer of composite materials, the adjustment of the equivalent of the equivalent capacitance and effective dielectric constant, the problem of high driving voltage of the existing electric wet display device is solved, and the effect of reducing the life of the driving voltage and extended device.

CN119355946AActive Publication Date: 2025-01-24LIGHT DISPLAY TECH (GUANGDONG) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411562634.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The driving voltage of existing electrowetted display devices is relatively high, making it difficult to apply widely used driving IC technologies such as liquid crystal display (LCD). At the same time, high driving voltage will lead to breakdown of the dielectric layer and hydrophobic layer, reducing the device life.

Method used

By designing the multi-layer dielectric hydrophobic layer structure of the composite material, the equivalent capacitance and effective dielectric constant can be controlled to reduce the driving voltage. Specific methods include coating amorphous polytetrafluoroethylene or perfluorocyclic polymer and other materials on the cellulose dielectric layer to form a hydrophobic layer, forming a pixel wall through a photolithography process, and optimizing the material thickness and structural design to improve etc. effective capacitance.

Benefits of technology

Realize the driving voltage of the electric wet display device, adapt to the wider display technology driver IC, and at the same time extend the life of the device to avoid the breakdown of the dielectric layer and the hydrophobic layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355946A_ABST
    Figure CN119355946A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and particularly discloses an electrowetting display with low driving voltage and a preparation method thereof. Comprising a composite material and a pixel wall, the composite material comprises a cellulose dielectric layer and a hydrophobic layer coated on the cellulose dielectric layer, the pixel wall is arranged above the hydrophobic layer; when the height of the pixel wall is 3.0-3.5 [mu] m, the equivalent capacitance of the composite material is 35-81 [mu] F / m < 2 >; when the height of the pixel wall is 5.0-5.5 [mu] m, the equivalent capacitance of the composite material is 58-81 [mu] F / m < 2 >. The thickness of the single-layer or multi-layer dielectric hydrophobic material is designed, so that the equivalent capacitance Ceq and the effective dielectric constant are regulated and controlled. When the thickness of the HF layer is reduced from 400 nm and 300 nm to 200 nm, Vd can be reduced from 17 V and 14 V to 9 V. Therefore, the enhancement of the equivalent capacitance Ceq plays a decisive role in reducing the driving voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to an electrowetting display with a low driving voltage and a preparation method thereof. Background Art

[0002] Electrowetting display (EWD) technology is to change the wettability of liquid on dielectric hydrophobic materials by electric drive, so that the droplets spread or shrink. After the integrated display, it can produce perceptible optical changes, with the characteristics of fast response time, low voltage and low power consumption. At present, the driving voltage of most EWD devices is relatively high (15-30V), and a customized electrophoretic display (EPD) driver IC is required. If the driving voltage of EWD devices is reduced, it will be possible to apply the currently widely used liquid crystal display (LCD) and other driver IC technologies. In addition, the lower driving voltage can further improve the life of the device, prevent the dielectric layer and the hydrophobic layer from breaking down when working under a large driving voltage, and greatly promote the replacement of EWD device driver ICs.

[0003] The voltage range of LCD driver IC for TFT-LCD display is 3-18V, which provides the necessary voltage for larger and higher resolution screens. Therefore, if the maximum driving voltage of LCD driver IC is 18V, the DC drive system of EWD device is connected, and the maximum voltage of AC drive system is ±9V. Therefore, it is necessary to provide an electrowetting display with low driving voltage and its preparation method, so as to reduce the driving voltage of reflective electrowetting device. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides an electrowetting display with low driving voltage and a preparation method thereof, thereby reducing the driving voltage of a reflective electrowetting device.

[0005] A first aspect of the present invention provides an electrowetting display with a low driving voltage.

[0006] Specifically, they include composite materials and pixel walls;

[0007] The composite material comprises a cellulose-based dielectric layer and a hydrophobic layer coated on the cellulose-based dielectric layer;

[0008] The pixel wall is above the hydrophobic layer;

[0009] When the height of the pixel wall is 3.0-3.5 μm, the equivalent capacitance of the composite material is 35-81 μF / m 2 ;

[0010] When the height of the pixel wall is 5.0-5.5 μm, the equivalent capacitance of the composite material is 58-81 μF / m 2.

[0011] Preferably, when the height of the pixel wall is 3.5 μm, the equivalent capacitance of the composite material is 35 to 81 μF / m 2 .

[0012] Further preferably, when the height of the pixel wall is 3.5 μm, the equivalent capacitance of the composite material is 35.1 to 80.2 μF / m 2 .

[0013] Preferably, when the height of the pixel wall is 5.5 μm, the equivalent capacitance of the composite material is 58 to 81 μF / m 2 .

[0014] Further preferably, when the height of the pixel wall is 5.5 μm, the equivalent capacitance of the composite material is 58.3 to 80.2 μF / m 2 .

[0015] Preferably, the effective dielectric constant of the composite material is 3 to 8C 2 / (N·M 2 ).

[0016] Further preferably, the effective dielectric constant of the composite material is 3.5 to 8C 2 / (N·M 2 ).

[0017] More preferably, the effective dielectric constant of the composite material is 3.5 to 7.9C 2 / (N·M 2 ).

[0018] Preferably, the thickness of the cellulose-based dielectric layer is 200-1000 nm.

[0019] Preferably, when the height of the pixel wall is 3.0 to 3.5 μm, the thickness of the hydrophobic layer is 200 to 400 nm;

[0020] When the height of the pixel wall is 5.0-5.5 μm, the thickness of the hydrophobic layer is 200-205 nm.

[0021] Further preferably, when the height of the pixel wall is 3.5 μm, the thickness of the hydrophobic layer is 200 to 400 nm;

[0022] When the height of the pixel wall is 5.5 μm, the thickness of the hydrophobic layer is 200-205 nm.

[0023] More preferably, when the height of the pixel wall is 3.5 μm, the thickness of the hydrophobic layer is 200 to 400 nm;

[0024] When the height of the pixel wall is 5.5 μm, the thickness of the hydrophobic layer is 200 nm.

[0025] Preferably, the material of the cellulose-based dielectric layer includes at least one of cyanoethyl cellulose, hydroxypropyl cellulose and cellulose acetate.

[0026] Preferably, the material of the hydrophobic layer includes any one of amorphous polytetrafluoroethylene, perfluorocyclic polymer and polytetrafluoroethylene.

[0027] More preferably, the amorphous polytetrafluoroethylene is Hyflon AD 40.

[0028] More preferably, the perfluorocyclic polymer is Cytop.

[0029] More preferably, the polytetrafluoroethylene is Teflon.

[0030] A second aspect of the present invention provides a method for preparing an electrowetting display.

[0031] Specifically, the following steps are included:

[0032] (1) dissolving the material of the cellulose dielectric layer in a solvent, and preparing the cellulose dielectric layer through multiple steps of spin coating, pre-curing, and heating; then dissolving the material of the hydrophobic layer in a solvent to prepare a hydrophobic layer coating solution, and then spin coating the hydrophobic layer coating solution on the surface of the cellulose dielectric layer, and then pre-curing and heating to prepare the composite material;

[0033] (2) treating the hydrophobic layer in the composite material to be hydrophilic, pre-curing it on a hot plate, and then performing mask exposure molding through a photolithography process to obtain a layer of pixel wall on the hydrophobic layer;

[0034] (3) The pixel wall forms a pixel grid structure, which is then placed on a hot plate for secondary curing, and a developer is prepared for development, cleaning, and high-temperature reflux to restore the hydrophobicity of the hydrophobic layer. The colored ink is filled in a pure water environment, and the package is encapsulated to obtain the electrowetting display.

[0035] Preferably, in step (2), the exposure time of the mask is 10 to 50 seconds.

[0036] Further preferably, in step (2), the exposure time of the mask is 10 to 30 seconds.

[0037] Preferably, in step (3), the developer comprises a KOH solution.

[0038] Preferably, the concentration of the KOH solution is 0.1-0.6 wt %.

[0039] More preferably, the concentration of the KOH solution is 0.4-0.6 wt %.

[0040] More preferably, the concentration of the KOH solution is 0.4 wt %.

[0041] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0042] The present invention designs the thickness of a single layer or multiple layers of dielectric hydrophobic material to adjust the equivalent capacitance C eq The effective dielectric constant is related to the size of the dielectric constant, thus providing a design guideline for multilayer dielectric hydrophobic layer materials for subsequent low driving voltage device research. When the pixel wall height is 3.5μm and a fixed CEC layer of 650nm is used, and the thickness of the HF layer is reduced from 400nm, 300nm to 200nm, V d It can be reduced from 17V, 14V to 9V. Therefore, the equivalent capacitance C eq The enhancement of plays a decisive role in reducing the driving voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The electrowetting curves of the double-layer composite structure with different thickness combinations;

[0044] Figure 2 This is a schematic structural diagram of the electrowetting display of Example 1;

[0045] Figure 3 The corresponding aperture ratio diagram of EWD devices with different CEC layer thicknesses under different applied voltages;

[0046] Figure 4 The corresponding aperture ratio diagrams of EWD devices with different combinations of double layers under different applied voltages;

[0047] Figure 5 CV curves of double-layer composite material structure EWD devices with different pixel wall heights;

[0048] Figure 6 is the equivalent capacitance (C eq ) and the applied voltage capacitance value (C dv ) comparison chart. DETAILED DESCRIPTION

[0049] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0050] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0051] Example 1

[0052] A low-driving-voltage electrowetting display and a preparation method thereof.

[0053] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 80.2 μF / m 2 , the effective dielectric constant of the composite material is 3.62C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 200 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0054] Preparation method:

[0055] (1) Dissolving cyanoethyl cellulose fibrous solid in DMF solvent, placing on an ultrasonic magnetic stirrer at 800 rpm for 1 hour, placing on a 40° C. hot plate for 10 minutes, leaving the solution to stand for 8 hours, and filtering through a 1 μm organic filter membrane twice to obtain a 3 wt% cyanoethyl cellulose dielectric coating solution;

[0056] Before spin coating, the solution can be ultrasonically treated for 10 minutes, and the air dust (impurities that affect spin coating film formation) that may be on the ITO glass can be blown off with a nitrogen gun, and ITO glass (TP-120, thickness 0.7 mm, resistance 120Ω) is prepared as a spin coating substrate, and the substrate pretreatment step is performed, the substrate pretreatment (the ITO glass is placed in ultrapure water / alcohol for 10 minutes of ultrasonic cleaning twice, and each cleaning is blown dry with a nitrogen gun, and after cleaning, it is transferred to a UV-ozone cleaning machine for 10 minutes of UV-ozone physical-chemical cleaning (removing organic pollutants on the ITO surface and hydroxylating the surface of the ITO substrate);

[0057] The solution was subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, then spin coating at 1200 rpm for 65 s), first pre-curing (pre-curing treatment was performed on a 40° C. hot plate for 3 min), and first heating (heating at 160° C. in a dust-free oven for 1.5 h) to volatilize the residual organic solvent, thereby obtaining a 200 nm cyanoethyl cellulose dielectric layer;

[0058] Hyflon AD 40 powder was then dissolved in Galden D02 solvent to prepare a 3wt% hydrophobic layer coating solution, the solution was ultrasonically treated for 10 minutes, and then the solution was spin-coated on the surface of a 200nm cyanoethyl cellulose dielectric layer by multi-step spin coating (first spin coating at 300rpm for 10s, then spin coating at 2400rpm for 65s), the spin coating time was 65s, and the solution was allowed to stand for 10min after spin coating, and subjected to a second pre-curing (placed on an 85°C hot plate for 1.5min for pre-curing treatment) and a second heating (placed in a dust-free oven at 185°C for 1h) to volatilize the residual organic solvent to obtain a composite material.

[0059] (2) The composite material was modified to be hydrophilic by a reactive ion etcher (power 5W, time 6s), and then HN-008 photoresist solution was spin-coated, and the solution was spin-coated in multiple steps (spin-coated at 500rpm for 10s, and then spin-coated at 1100rpm for 65s) to prepare a layer of pixel wall. After hot plate pre-curing (temperature 110°C, time 2.5min), the photolithography process was used for 18s mask exposure molding (preparing a pixel wall with a height of 3.5μm), and a pixel grid structure was prepared. It was then placed on a hot plate (temperature 110°C, time 2.5min) for secondary curing, and a 0.4wt% KOH solution developer was prepared for development. It was used twice to clean the photoresist that was not cured by UV light for 1min each, and the residual KOH solution was removed by pure water rinsing for 1min. The pixel grid structure is cleaned again by the Descum process using a reactive ion etcher to remove the residual photoresist and other organic impurities such as developer on the surface, and the development is repeated. After completion, high-temperature reflow is performed to restore the hydrophobicity of the hydrophobic layer. Finally, the sheet with the pixel grid structure is filled with colored ink in a pure water environment. After the filling is completed, the prepared upper substrate (ITO glass) is packaged with a glue frame to obtain an electrowetting display.

[0060] Example 2

[0061] A low-driving-voltage electrowetting display and a preparation method thereof.

[0062] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprises a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 66.2 μF / m 2 , the effective dielectric constant of the composite material is 6.36C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 650 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0063] Preparation method:

[0064] The difference from Example 1 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 1100 rpm for 65 s) to obtain a 650 nm cyanoethyl cellulose dielectric layer.

[0065] Example 3

[0066] A low-driving-voltage electrowetting display and a preparation method thereof.

[0067] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 58.3 μF / m 2 The effective dielectric constant of the composite material is 7.90C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 1000 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0068] Preparation method:

[0069] The difference from Example 1 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 700 rpm for 65 s) to obtain a 1000 nm cyanoethyl cellulose dielectric layer.

[0070] Example 4

[0071] A low-driving-voltage electrowetting display and a preparation method thereof.

[0072] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprises a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 51.8 μF / m 2 , the effective dielectric constant of the composite material is 4.1C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 400 nm, and the thickness of the Hyflon hydrophobic layer is 300 nm.

[0073] Preparation method:

[0074] The difference from Example 1 is that the solution in step (1) is replaced with a 5 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 2200 rpm for 10 s, and then spin coating at 1500 rpm for 65 s) to obtain a 400 nm cyanoethyl cellulose dielectric layer.

[0075] At the same time, the hydrophobic layer coating solution was replaced with single-step spin coating and spin-coated on the surface of the 400nm cyanoethyl cellulose dielectric layer at a speed of 1200rpm (65s). After standing, pre-curing and volatilizing the residual organic solvent in a dust-free oven, a 300nm Hyflon hydrophobic layer was completed to obtain a composite material.

[0076] Example 5

[0077] A low-driving-voltage electrowetting display and a preparation method thereof.

[0078] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprises a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 48.2 μF / m 2 , the effective dielectric constant of the composite material is 5.17C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 650 nm, and the thickness of the Hyflon hydrophobic layer is 300 nm.

[0079] Preparation method:

[0080] The difference from Example 2 is that a hydrophobic layer coating solution is used, the single-step spin coating speed is changed, and the surface of the 650nm cyanoethyl cellulose dielectric layer is spin-coated at a speed of 1200rpm (65s). After standing, pre-curing and volatilizing the residual organic solvent in a dust-free oven, a 300nm Hyflon hydrophobic layer is completed to obtain a composite material.

[0081] Example 6

[0082] A low-driving-voltage electrowetting display and a preparation method thereof.

[0083] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 43.9 μF / m 2, the effective dielectric constant of the composite material is 6.44C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 1000 nm, and the thickness of the Hyflon hydrophobic layer is 300 nm.

[0084] Preparation method:

[0085] The difference from Example 4 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 700 rpm for 65 s) to obtain a 1000 nm cyanoethyl cellulose dielectric layer.

[0086] Example 7

[0087] A low-driving-voltage electrowetting display and a preparation method thereof.

[0088] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 37.9 μF / m 2 The effective dielectric constant of the composite material is 4.49C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 650 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0089] Preparation method:

[0090] The difference from Example 2 is that a hydrophobic layer coating solution is used, the single-step spin coating speed is changed, and the surface of the 650nm cyanoethyl cellulose dielectric layer is spin-coated at a speed of 720rpm (65s). After standing, pre-curing and volatilizing the residual organic solvent in a dust-free oven, a 400nm Hyflon hydrophobic layer is completed to obtain a composite material.

[0091] Example 8

[0092] A low-driving-voltage electrowetting display and a preparation method thereof.

[0093] An electrowetting display with low driving voltage includes a composite material and a pixel wall; the composite material includes a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance of the composite material is 35.1 μF / m 2 , the effective dielectric constant of the composite material is 5.56C2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 1000 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0094] Preparation method:

[0095] The difference from Example 7 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 700 rpm for 65 s) to obtain a 1000 nm cyanoethyl cellulose dielectric layer.

[0096] Example 9

[0097] A low-driving-voltage electrowetting display and a preparation method thereof.

[0098] A low-driving-voltage electrowetting display includes a composite material and a pixel wall; the composite material includes a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 80.2 μF / m 2 , the effective dielectric constant of the composite material is 3.62C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 200 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0099] Preparation method:

[0100] The difference from Example 1 is that in the preparation of the pixel wall, the rotation speed of the spin coating of the HN-008 photoresist solution is changed, and the solution is single-step spin coated at a rotation speed of 580 rpm for 65 seconds to prepare a thicker 5.5 μm pixel wall.

[0101] Example 10

[0102] A low-driving-voltage electrowetting display and a preparation method thereof.

[0103] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 67.5 μF / m 2 The effective dielectric constant of the composite material is 6.10C 2 / (N·M 2). The thickness of the cyanoethyl cellulose dielectric layer is 600 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0104] Preparation method:

[0105] The difference from Example 9 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 1200 rpm for 65 s) to obtain a 600 nm cyanoethyl cellulose dielectric layer.

[0106] Embodiment 11

[0107] A low-driving-voltage electrowetting display and a preparation method thereof.

[0108] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprises a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 58.3 μF / m 2 The effective dielectric constant of the composite material is 7.90C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 1000 nm, and the thickness of the Hyflon hydrophobic layer is 200 nm.

[0109] Preparation method:

[0110] The difference from Example 9 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at 300 rpm for 10 s, and then spin coating at 700 rpm for 65 s) to obtain a 1000 nm cyanoethyl cellulose dielectric layer.

[0111] Comparative Example 1

[0112] A low-driving-voltage electrowetting display and a preparation method thereof.

[0113] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprises a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 43.9 μF / m 2 , the effective dielectric constant of the composite material is 2.85C 2 / (N·M 2). The thickness of the cyanoethyl cellulose dielectric layer is 200 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0114] Preparation method:

[0115] The difference from Example 9 is that a hydrophobic layer coating solution is used, the single-step spin coating speed is changed, and the surface of the 200nm cyanoethyl cellulose dielectric layer is spin-coated at a speed of 720rpm (65s). After standing, pre-curing and volatilizing the residual organic solvent in a dust-free oven, a 400nm Hyflon hydrophobic layer is completed to obtain a composite material.

[0116] Comparative Example 2

[0117] A low-driving-voltage electrowetting display and a preparation method thereof.

[0118] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 40.1 μF / m 2 , the effective dielectric constant of the composite material is 3.62C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 400 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0119] Preparation method:

[0120] The difference from Comparative Example 1 is that the solution in step (1) is replaced with a 5 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at a rotation speed of 300 rpm for 10 s, and then spin coating at a rotation speed of 1500 rpm for 65 s) to obtain a 400 nm cyanoethyl cellulose dielectric layer.

[0121] Comparative Example 3

[0122] A low-driving-voltage electrowetting display and a preparation method thereof.

[0123] A low-drive-voltage electrowetting display comprising a composite material and a pixel wall; the composite material comprising a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 37.9 μF / m 2 The effective dielectric constant of the composite material is 4.49C 2 / (N·M 2). The thickness of the cyanoethyl cellulose dielectric layer is 650 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0124] Preparation method:

[0125] The difference from Comparative Example 1 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating in step (1) is changed, and the solution is subjected to multi-step spin coating (first spin coating at a rotation speed of 300 rpm for 10 s, and then spin coating at a rotation speed of 1100 rpm for 65 s) to obtain a 650 nm cyanoethyl cellulose dielectric layer.

[0126] Comparative Example 4

[0127] A low-driving-voltage electrowetting display and a preparation method thereof.

[0128] A low-driving-voltage electrowetting display includes a composite material and a pixel wall; the composite material includes a cyanoethyl cellulose dielectric layer and a Hyflon hydrophobic layer coated on the cyanoethyl cellulose dielectric layer; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 5.5 μm, and the equivalent capacitance of the composite material is 35.1 μF / m 2 , the effective dielectric constant of the composite material is 5.56C 2 / (N·M 2 ). The thickness of the cyanoethyl cellulose dielectric layer is 1000 nm, and the thickness of the Hyflon hydrophobic layer is 400 nm.

[0129] Preparation method:

[0130] The difference from Comparative Example 1 is that the solution in step (1) is replaced with a 6 wt % cyanoethyl cellulose dielectric layer coating solution, and the rotation speed of the multi-step spin coating is changed. The solution is subjected to multi-step spin coating (first spin coating at a rotation speed of 300 rpm for 10 s, and then spin coating at a rotation speed of 700 rpm for 65 s) to obtain a 1000 nm cyanoethyl cellulose dielectric layer.

[0131] Comparative Example 5

[0132] A low-driving-voltage electrowetting display and a preparation method thereof.

[0133] The low-drive-voltage electrowetting display includes a Hyflon hydrophobic layer and a pixel wall; the pixel wall is above the Hyflon hydrophobic layer. The height of the pixel wall is 3.5 μm, and the equivalent capacitance is 25.3 μF / m 2 , the effective dielectric constant is 2.00C 2 / (N·M 2 ). The thickness of the Hyflon hydrophobic layer is 700nm.

[0134] Preparation method:

[0135] Hyflon AD 40 powder was dissolved in Galden D02 solvent to prepare a 3 wt % hydrophobic layer coating solution.

[0136] Before spin coating, the solution can be ultrasonically treated for 10 minutes, and the air dust (impurities that affect spin coating film formation) that may be on the ITO glass can be blown off with a nitrogen gun, and ITO glass (TP-120, thickness 0.7 mm, resistance 120Ω) is prepared as a spin coating substrate, and the substrate pretreatment step is performed, the substrate pretreatment (the ITO glass is placed in ultrapure water / alcohol for 10 minutes of ultrasonic cleaning twice, and each cleaning is blown dry with a nitrogen gun, and after cleaning, it is transferred to a UV-ozone cleaning machine for 10 minutes of UV-ozone physical-chemical cleaning (removing organic pollutants on the ITO surface and hydroxylating the surface of the ITO substrate);

[0137] The 3wt% hydrophobic layer coating solution was ultrasonically treated for 10 minutes, and then the 3wt% hydrophobic layer coating solution was spin-coated on the surface of the 200nm cyanoethyl cellulose dielectric layer at a speed of 340rpm. The spin coating time was 65s. After spin coating, it was allowed to stand for 10 minutes, and then subjected to a second pre-curing (placed on an 85°C hot plate for 1.5 minutes for pre-curing treatment) and a second heating (placed in a dust-free oven and heated at 185°C for 1 hour) to volatilize the residual organic solvent to obtain a composite material.

[0138] Comparative Example 6

[0139] A composite material.

[0140] Before spin coating, the solution can be ultrasonically treated for 10 minutes, and the air dust (impurities that affect spin coating film formation) that may be on the ITO glass can be blown off with a nitrogen gun, and ITO glass (TP-120, thickness 0.7 mm, resistance 120Ω) is prepared as a spin coating substrate, and the substrate pretreatment step is performed, the substrate pretreatment (the ITO glass is placed in ultrapure water / alcohol for 10 minutes of ultrasonic cleaning twice, and each cleaning is blown dry with a nitrogen gun, and after cleaning, it is transferred to a UV-ozone cleaning machine for 10 minutes of UV-ozone physical-chemical cleaning (removing organic pollutants on the ITO surface and hydroxylating the surface of the ITO substrate);

[0141] The HN-018 solution was spin-coated at 1750 rpm for 65 seconds by single-step spin coating, pre-cured (placed on a 110°C hot plate for 2.5 minutes for pre-curing treatment), and after pre-curing, the entire surface was exposed using a photolithography machine for 35 seconds, and then heated for the first time (placed in a dust-free oven at 190°C for 1.5 hours) to volatilize the residual organic solvent, thereby obtaining a 400 nm HN-018 dielectric layer;

[0142] The Hyflon AD 40 powder was then dissolved in Galden D02 solvent to obtain a 3wt% hydrophobic layer coating solution. The solution was ultrasonically treated for 10 minutes, and then spin-coated on the surface of the 200nm cyanoethyl cellulose dielectric layer at a speed of 720rpm for 65 seconds. After spin coating, the solution was allowed to stand for 10 minutes, and then subjected to a second pre-curing (placed on an 85°C hot plate for 1.5 minutes for pre-curing treatment) and a second heating (placed in a dust-free oven at 185°C for 1 hour) to volatilize the residual organic solvent, completing a 400nm Hyflon layer to obtain a (400HN+400HF) composite material.

[0143] Comparative Example 7

[0144] A composite material.

[0145] The difference from Comparative Example 6 is that a Hyflon solution is used, the rotation speed of the single-step spin coating is changed, and the surface of the 400nm HN-018 dielectric layer is spin-coated at a speed of 1200rpm (65s). After standing, pre-curing and volatilizing the residual organic solvent in a dust-free oven, a 400nm Hyflon hydrophobic layer is completed to obtain a (400HN+300HF) composite material.

[0146] Performance testing:

[0147] 1. Opening rate (R open )Detection:

[0148] Capacitance-voltage (CV) curves were recorded using an LCR digital bridge tester (TH2828) with a voltage ramp rate of 1 V / step. The aperture ratio was measured using a custom setup consisting of a microscope, wireless power source, and light source. The data was calculated using a program created in Visual Studio 2018 to obtain the aperture ratio. Among them A Oil(V) is the area occupied by the oil when V is applied on the electrowetting display device, A Pixel is the total area of ​​the pixel.

[0149] 2. Driving voltage (V d )Detection:

[0150] The driving voltage is the voltage that is used to make the aperture ratio reach 60%. The specific detection method is: use a picoammeter (model 6487, Keithley) as a DC power supply, set the voltage to a linear voltage, the interval is 250ms, start from a low voltage to test whether it can be opened to 60%, and when the applied linear voltage makes the aperture ratio detection exceed 60%, record the voltage and aperture ratio data.

[0151] Table 1 Aperture ratio and driving voltage results of various embodiments and comparative examples

[0152] <![CDATA[R open (%)]]> <![CDATA[V d (V)<!-- 8 --> ]]> Example 1 61.9 9 Example 2 62.1 9 Example 3 60.4 9 Example 4 61.4 14 Example 5 61.1 14 Example 6 61.2 14 Example 7 60.3 17 Example 8 61.5 17 Example 9 61.4 13 Example 10 62.7 15 Embodiment 11 60.8 15 Comparative Example 1 60.3 23 Comparative Example 2 62.2 23 Comparative Example 3 61.3 23 Comparative Example 4 60.2 23 Comparative Example 5 60.8 25

[0153] In the electrowetting curve, Figure 1 In (a), the electrowetting (EWOD) curves of double-layer dielectrics with different thicknesses are compared. When the total thickness is about 800nm, the 200 / 600nm combination of the Hyflon hydrophobic layer / cyanoethyl cellulose dielectric layer (hereinafter referred to as HF layer / CEC layer) double layer shows better electrowetting performance. The combination of a thinner HF layer and a thicker CEC dielectric layer improves the overall wetting performance of the double-layer structure. Under an applied voltage of 60V, the contact angle is modulated to 65.1°. This can be further applied to the EWOD system to achieve a θ of 51.2° at a lower voltage of 48V. CA (from 116.3° to 65.1°). Figure 1 (b) shows the comparison of electrowetting curves of three different CEC layer thicknesses without changing the HF layer thickness. The voltage threshold for the droplet to start changing is lower for the double layer with a thinner overall thickness, but the overall electrowetting curves are relatively similar. The change of the CEC layer does not have a greater impact on the electrowetting curve than the change of the HF layer, but the introduction of the CEC layer significantly improves the EWOD performance. Figure 1 (c) and (d) show that the double-layer HF / CEC structure and the double-layer HF / HN-018(HN) have similar reversible electrowetting behavior and low hysteresis characteristics, but the optimized 200nm HF / 600nm CEC double layer has a better electrowetting curve and exhibits better contact angle modulation.

[0154] From the comparison of the opening ratio of electrowetting displays (EWD devices) with different layer thicknesses, it can be seen that Figure 3 In the case of a fixed HF layer thickness, the driving voltage of the EWD devices with three different CEC layer thicknesses varies little, which also corresponds to the electrowetting curve. Figure 1 (b) trend. Figure 4 It can be seen that when the thickness of the CEC layer remains unchanged, the driving voltage and opening voltage of the double-layer EWD device are greatly reduced by reducing the thickness of the HF layer, proving that reducing the thickness of the HF layer can effectively improve the performance. The driving voltage can be reduced to 9V in the optimized 200nm HF / 600nm CEC double-layer structure device, which indicates that this system will have the potential to apply the currently widely used liquid crystal display (LCD) and other driver IC technologies, greatly promoting the replacement of EWD device driver ICs.

[0155] Figure 5 The CV curves of double-layer EWD devices with different pixel wall heights show the capacitance curves of EWD devices under applied voltage. Figure 5The HF thickness of (a) is thinner, so the change of CEC thickness has a more obvious effect on the CV curve. However, under normal HF thickness, the change of CEC thickness has little effect on the double-layer EWD device. Figure 5 (e) and (f) verify the importance of HF thickness. When the thickness of the CEC layer remains unchanged, the thickness of the HF layer plays a decisive role in the equivalent capacitance, thereby affecting the driving voltage.

[0156] This study found that the driving voltage of the electrowetting display device can be reduced by improving the equivalent capacitance and effective dielectric constant of the double-layer dielectric hydrophobic material, and proposed a theoretical basis for reducing the driving voltage. The specific relationship between the dielectric constant and capacitance can be explained according to the electrowetting Young-Lippanman equation and the series equivalent capacitor equation:

[0157] From the above formula, it can be seen that the ability to achieve large contact angle changes at low voltages is highly dependent on the total capacitance C of the dielectric multilayer. eq Therefore, the present invention calculates the equivalent capacitance (C eq ) and effective dielectric constant (ε R ) to achieve the design of dielectric hydrophobic double-layer functional materials in low driving voltage EWD devices. In the derivation of formula (2), it can be obtained that due to the calculation of the series capacitor, the equivalent capacitance value depends more on the thickness d of the hydrophobic layer HF HF , when the HF layer is thicker, the equivalent capacitance is smaller, and the influence of the thickness change of the CEC layer is smaller than that of the HF layer. Therefore, in a multi-layer design, a layer with a small dielectric constant often plays a greater role. This allows EWD to adapt to driver ICs of a wider range of display technologies, while reducing the driving voltage, allowing the device to work at a reduced voltage, and also preventing dielectric breakdown problems in electronic devices.

[0158] Table 1 shows examples of different device structures. After the equivalent capacitance Ceq and effective dielectric constant are improved, for example, the equivalent capacitance Ceq of the double-layer equivalent capacitor of 300nm HF / 400nm CEC in Example 4 is eq It can be calculated to be 51.8μF / m 2 , which is about twice the thickness of the 700nm HF in Comparative Example 5. The 700nm HF monolayer has a C eq The value is only 25.3μF / m 2 , and after optimization, the double layer C of 200nm HF / 600nm CEC in Example 10 eq Can reach higher, 67.5μF / m 2In comparative example 2, the thickness of the HF layer was increased by only 100 nm, and it was found that the Ceq of the double layer of 400 nm HF / 400 nm CEC increased from 51.8 μF / m 2 Reduced to 40.1μF / m 2 , the equivalent capacitance becomes lower and changes greatly. In Examples 5 and 6, the CEC layer thickness is increased by 250nm and 600nm, and it is found that the corresponding double-layer C eq 48.2 and 43.9 μF / m 2 , although it also decreases, the change range is much smaller than that of the HF layer. The above results are calculated by formula (2), and the overall capacitance C of the EWD device is tested at the same time. dv ,See Figure 6 , which also shows the same trend as the theoretical calculation, verifying that the effective capacitance of the dielectric hydrophobic material plays a key role in the overall performance of the device.

[0159] At the same time, the effective dielectric constants in Table 1 can also be calculated by formula (2), such as the dielectric constant of the 700nm HF single layer in Comparative Example 5 is only 2.00. The dielectric constant of the double layer of 300nm HF / 400nm CEC in Example 4 is 4.10, and the dielectric constant of the double layer of 200nm HF / 600nm CEC in Example 10 is 6.10. In Comparative Example 2, only the thickness of the HF layer is increased by 100nm, and it is found that the double layer of 400nm HF / 400nm CEC is reduced from 4.10 to 3.62, and the effective dielectric constant becomes lower. In Examples 5 and 6, the thickness of the CEC layer is increased by 250nm and 600nm, and it is found that the effective dielectric constants of the corresponding double layers are 5.17 and 6.44. The improvement of the dielectric constant can be obtained from formula (1), and the modulation of the same contact angle is completed at a lower voltage, but the problem of contact angle saturation will also be encountered. This explains what was said before: under the same HF thickness, the opening voltage of the thicker CEC double layer will be lower, and the contact angle can be driven at a lower voltage. After the EWD device is packaged, the EWD device with higher capacitance and effective dielectric constant shows a lower driving voltage. Formula (1) shows that increasing the effective dielectric constant of the composite material can reduce the driving voltage of the electrowetting device.

[0160] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. A low driving voltage electrowetting display, characterized in that: including composite materials and pixel walls; The composite material comprises a cellulose-based dielectric layer and a hydrophobic layer coated on the cellulose-based dielectric layer; The pixel wall is above the hydrophobic layer; When the height of the pixel wall is 3.0-3.5 μm, the equivalent capacitance of the composite material is 35-81 μF / m 2 ; When the height of the pixel wall is 5.0-5.5 μm, the equivalent capacitance of the composite material is 58-81 μF / m 2 .

2. The electrowetting display according to claim 1, characterized in that: The effective dielectric constant of the composite material is 3 to 8C 2 / (N·M 2 ).

3. The electrowetting display according to claim 1, characterized in that: The thickness of the cellulose dielectric layer is 200-1000 nm.

4. The electrowetting display according to claim 1, characterized in that: When the height of the pixel wall is 3.0-3.5 μm, the thickness of the hydrophobic layer is 200-400 nm; When the height of the pixel wall is 5.0-5.5 μm, the thickness of the hydrophobic layer is 200-205 nm.

5. The electrowetting display according to claim 1, characterized in that: The material of the cellulose dielectric layer includes at least one of cyanoethyl cellulose, hydroxypropyl cellulose and cellulose acetate.

6. The electrowetting display according to claim 1, characterized in that: The material of the hydrophobic layer includes any one of amorphous polytetrafluoroethylene, perfluorocyclic polymer and polytetrafluoroethylene.

7. The method for preparing an electrowetting display according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) dissolving the material of the cellulose dielectric layer in a solvent, and preparing the cellulose dielectric layer through multiple steps of spin coating, pre-curing, and heating; then dissolving the material of the hydrophobic layer in a solvent to prepare a hydrophobic layer coating solution, and then spin coating the hydrophobic layer coating solution on the surface of the cellulose dielectric layer, and then pre-curing and heating to prepare the composite material; (2) treating the hydrophobic layer in the composite material to be hydrophilic, pre-curing it on a hot plate, and then performing mask exposure molding through a photolithography process to obtain a layer of pixel wall on the hydrophobic layer; (3) The pixel wall forms a pixel grid structure, which is then placed on a hot plate for secondary curing, and a developer is prepared for development, cleaning, and high-temperature reflux to restore the hydrophobicity of the hydrophobic layer. The colored ink is filled in a pure water environment, and the package is encapsulated to obtain the electrowetting display.

8. The preparation method according to claim 7, characterized in that: In step (2), the exposure time of the mask is 10 to 50 seconds.

9. The preparation method according to claim 7, characterized in that: In step (3), the developer includes a KOH solution.

10. The preparation method according to claim 9, characterized in that: The concentration of the KOH solution is 0.1-0.6 wt %.

Citation Information

Patent Citations

  • Display systems

    CN103493123A

  • Oil breakdown controlled opening system used for EFD device and manufacturing method thereof

    CN103901606A

  • Electrowetting front plate and preparation method thereof and electrowetting display device

    CN105204156A

  • Reducing Visual Artifacts and Reducing Power Consumption in Electrowetting Displays

    US20160189638A1

  • Display device, display module including the display device, and electronic device including the display device or the display module

    US20160282686A1